2005
DOI: 10.1016/j.jom.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Service Guarantee Strength: The key to service quality

Abstract: While most authors describe a service guarantee as a ''zero-one variable'' indicating the presence or absence of an explicit written service guarantee, this paper develops a construct called ''Service Guarantee Strength'' (SGS) that is a continuous variable. This construct measures the degree to which a firm sets clear service quality standards for itself on dimensions that customers care about, and has an formal policy for quickly giving meaningful compensation to customers when these standards are not met.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 39 publications
2
44
0
3
Order By: Relevance
“…In the study, the measurements for customer satisfaction were modified based on the previous studies of Parasuraman et al (1988), Homburg and Stock (2004), Chung and Lee (2005), Hay and Hill (2006), Friesner et al (2008), and Yee et al (2008). This study adapted measurement items of the customer loyalty suggested by Chung and Lee (2005) and Hay and Hill (2006).…”
Section: The Service Industries Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, the measurements for customer satisfaction were modified based on the previous studies of Parasuraman et al (1988), Homburg and Stock (2004), Chung and Lee (2005), Hay and Hill (2006), Friesner et al (2008), and Yee et al (2008). This study adapted measurement items of the customer loyalty suggested by Chung and Lee (2005) and Hay and Hill (2006).…”
Section: The Service Industries Journalmentioning
confidence: 99%
“…This study adapted measurement items of the customer loyalty suggested by Chung and Lee (2005) and Hay and Hill (2006). Figure 1 shows the proposed research model describing how health-care HPWS affect employee reaction, service quality, customer satisfaction, and customer loyalty.…”
Section: The Service Industries Journalmentioning
confidence: 99%
“…The instrument used was the common measurement behavior with scales and questionnaire method adapted from the work of Hays and Hill (2006), Shahril (2014), Aziz (2007) and Severt (2002) with the reliability or Cronbach's alpha for the questionnaire ranges above 0.8. These researchers work was adapted for this study because of their considerable researches in the field.…”
Section: Hotels (Four-star and Five-star) X 25 Employees = 500 Employeesmentioning
confidence: 99%
“…Whereas fragmented relationships, which amounted to simple information trading, constituted the principal relationship in the Web 1.0 era, network-based interaction becomes dominant in Web 2.0 and after. Information system researchers claim that, if OSNs are limited to establishing friendship between users with similar interests or people who know each other, requirements have recently been proposed for the vitalization of online communities and the expansion of their influence and lifestreams (Ebling et al, 2002;Hays & Hill, 2006). They also see a change in that communities centered on core users understand and accept the social embeddedness of individual constituents.…”
Section: Evolutionary Path and Framework Of Online Social Network Busmentioning
confidence: 99%